The effect of caffeine ingestion on delayed onset muscle soreness - Hurley, C. F.; Hatfield, D. L.; Riebe, D. A. (The Journal of Strength and Conditioning Research, 2013)
The beneficial effects of caffeine on aerobic activity and resistance training performance are well documented. However, less is known concerning caffeine's potential role in reducing perception of pain and soreness during exercise. In addition, there is no information regarding the effects of caffeine on delayed onset muscle soreness (DOMS). The primary purpose of this study was to examine the effect of caffeine ingestion on muscle soreness, blood enzyme activity, and performance after a bout of elbow flexion/extension exercise. Nine low-caffeine-consuming males (body mass: 76.68 ± 8.13 kg; height: 179.18 ± 9.35 cm; age: 20 ± 1 year) were randomly assigned to ingest either caffeine or placebo 1 hour before completing 4 sets of 10 bicep curls on a preacher bench, followed by a fifth set in which subjects completed as many repetitions as possible. Soreness and soreness on palpation intensity were measured using three 0-10 visual analog scales before exercise, and 24, 48, 72, 96, and 120 hours after exercise. After a washout period, subjects crossed over to the other treatment group. Caffeine ingestion resulted in significantly (p ? 0.05) lower levels of soreness on day 2 and day 3 compared with placebo. Total repetitions in the final set of exercise increased with caffeine ingestion compared with placebo. This study demonstrates that caffeine ingestion immediately before an upper-body resistance training out enhances performance. A further beneficial effect of sustained caffeine ingestion in the days after the exercise bout is an attenuation of DOMS. This decreased perception of soreness in the days after a strenuous resistance training workout may allow individuals to increase the number of training sessions in a given time period.